(untitled) (Research, Society and Development, 2021)
Hemangioma is characterized by the proliferation of blood vessels, being described as a vascular neoplasia or a vascular anomaly. It has a considerable incidence in the head and neck regions and in the oral cavity, most often it affects structures such as lips, tongue and jugal mucosa. Due to its location being commonly reported in the areas of operation of the dentist, knowledge of this neoplasm is of great importance. Its diagnosis is clinical, made with the aid of diascopy, a semiotechnical maneuver that causes blood flow and fading of the central staining of the lesion, indicating its vascular origin. Currently, among therapeutic alternatives, sclerotherapy has been widespread, due to the presentation of satisfactory clinical results. The aim of this study is to present the clinical case of a hemangioma located in the cheek mucosa in a pediatric, leukoderma, female pacient, who was accompanied by the parents to the clinic at the Academic League of Stomatology and Oral Medicine (LAEMO) of Universidade Católica de Brasília. His treatment was done through therapeutic sclerosis with monoethanolamineoleate (Ethamolin®), resulting in total lesion involution in 3 applications, in addition to no sign of recurrence after 3 months. In this case, it was possible to provide total regression of the lesion through non-surgical therapy, demonstrating the efficiencyand safety in the use of Ethamolin® for sclerotherapy in this type of neoplasia.